Unintended consequences of negative campaigning: Backlash and second-preference boost effects in a multi-party context. (August 2019) - Walter, Annemarie S; van der Eijk, Cees
This study examines effects of negative campaigning by political parties on citizens' electoral preferences in the 2015 General Election in England. We do so by using a large Internet panel study and an operationalisation of (perceived) negative campaigning that avoids social desirability. Our study acknowledges England's multiparty system by distinguishing between the campaign tones of all parties. Potential problems of endogeneity are addressed by leveraging the panel structure of the data and by extensive controls. We find that electoral preferences are weakened for parties engaging in negative campaigning and that this backlash effect gets stronger over the course of the campaign. We also find support for a second-preferences boost hypothesis: preferences for one's second-most preferred party are strengthened if its campaign is more positive than that of one's most-preferred party.